2019
DOI: 10.1111/nyas.14239
|View full text |Cite
|
Sign up to set email alerts
|

AcrB: a mean, keen, drug efflux machine

Abstract: Gram-negative bacteria are intrinsically resistant against cytotoxic substances by means of their outer membrane and a network of multidrug efflux systems, acting in synergy. Efflux pumps from various superfamilies with broad substrate preferences sequester and pump drugs across the inner membrane to supply the highly polyspecific and powerful tripartite resistance-nodulation-cell division (RND) efflux pumps with compounds to be extruded across the outer membrane barrier. In Escherichia coli, the tripartite ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
151
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(161 citation statements)
references
References 197 publications
(315 reference statements)
10
151
0
Order By: Relevance
“…Salmonella is an important Gram-negative pathogen, the prevalence of which is increasing especially in nosocomial settings. While there are many adaptive routes for the development of MDR in Salmonella [ 1 ], the role of the multidrug efflux-pumps in the process has been identified as one of the key mechanisms for escaping the antibiotic and biocide selective pressures [ 2 , 3 , 4 ]. The action of the resistance-nodulation-division (RND) transporter AcrB provides the principal antimicrobial resistance efflux function in Salmonella enterica serovar Typhimurium (from here on, S. Typhimurium) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella is an important Gram-negative pathogen, the prevalence of which is increasing especially in nosocomial settings. While there are many adaptive routes for the development of MDR in Salmonella [ 1 ], the role of the multidrug efflux-pumps in the process has been identified as one of the key mechanisms for escaping the antibiotic and biocide selective pressures [ 2 , 3 , 4 ]. The action of the resistance-nodulation-division (RND) transporter AcrB provides the principal antimicrobial resistance efflux function in Salmonella enterica serovar Typhimurium (from here on, S. Typhimurium) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…AcrB, the most studied transporter in the RND family, is a trimeric inner membrane transporter that confers resistance to a wide range of antibiotics (e.g., tetracycline, chloramphenicol, β-lactams, novobiocin, fusidic acid, nalidixic acid and fluoroquinolones), detergents (e.g., sodium dodecyl sulfate [SDS] and Triton X-100), various cationic dyes, disinfectants and even solvents [ 27 ]. The pSYC-acrB expression construct was transformed into the E .…”
Section: Resultsmentioning
confidence: 99%
“…As such, they represent a viable alternative to gain insights into the binding of compounds to AcrB. One of the earlier studies on this protein identified two distinct sub portions of the DP T , called "groove" and "cave" [44,45]. The groove region is located in the upper portion of the DP T , close to the so-called exit gate (EG , Table S1) [15], while the broader cave region is located at the bottom of the DP T .…”
Section: Introductionmentioning
confidence: 99%